2009
DOI: 10.1093/ndt/gfp470
|View full text |Cite
|
Sign up to set email alerts
|

Association of low serum 25-hydroxyvitamin D levels and high arterial blood pressure in the elderly

Abstract: Low serum 25(OH)-D levels were inversely and independently associated with BP. Supplemental measures to prevent hypovitaminosis D in this population would be important, not only to protect the skeletal system but also for the possible beneficial effects on the cardiovascular system and the BP regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
7
34
0
1
Order By: Relevance
“…This state of calciferol insufficiency is replicated in Spain, with results which we show in table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . The interlaboratory variation in the different methodologies used makes a rigorous comparison difficult, but the table illustrates clearly that, in spite of a theoretical climatological ease of vitamin D synthesis in Spain, the levels are similar to, or even lower than those reported for central Europe or Scandinavia, as has been described in earlier works 39 .…”
Section: State Of Vitamin D Insufficiency In Spainmentioning
confidence: 55%
See 1 more Smart Citation
“…This state of calciferol insufficiency is replicated in Spain, with results which we show in table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . The interlaboratory variation in the different methodologies used makes a rigorous comparison difficult, but the table illustrates clearly that, in spite of a theoretical climatological ease of vitamin D synthesis in Spain, the levels are similar to, or even lower than those reported for central Europe or Scandinavia, as has been described in earlier works 39 .…”
Section: State Of Vitamin D Insufficiency In Spainmentioning
confidence: 55%
“…Most of Spain is above the 35ºN parallel where the possibility of synthesising vitamin D in winter and spring is low, and because most Spanish people have darker skin which makes the synthesis of vitamin D more difficult 39 . We observed that in Spain, as in the rest of the world, insufficiency, or even true deficiency in vitamin D is already found in children or young people, and persists in adults, postmenopausal women (osteoporotic or not), and in older people who live in their own homes, and that it is even higher if they live in residential homes, with a seasonal variation which barley reaches normal levels after summer-autumn [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Although this high prevalence of low levels of vitamin D occurs due to inadequate exposure to sunlight, in older Spanish people lower levels have been described in the summer months due to the high temperatures which occur in the cities of southern Spain such as Murcia or Cordoba at this time of year, which are commonly between 30 and 40° C. The older people avoid being in the sun and prefer to remain indoors where the temperature is more comfortable.…”
Section: State Of Vitamin D Insufficiency In Spainmentioning
confidence: 99%
“…Regarding blood pressure, data from NHANES III (USA) showed an inverse correlation between SBP and vitamin D [12], and other studies have shown similar associations [37] [38]. The role of vitamin D in the reninangiotensin-aldosterone system is the most plausible explanation for the results [13].…”
Section: Discussionmentioning
confidence: 69%
“…50,51 The inverse relationship between levels of Vit D and hypertension has been assessed in several studies. [52][53][54] It is slightly more clear whether supplementation of Vit D decreases arterial pressure. 55,56 In our study, SBP and DBP levels were higher in individuals with MS than without MS.…”
Section: Resultsmentioning
confidence: 99%